Firm Value and the Choice of Offering Method in Initial Public Offerings - BOWER, NANCY L. (Journal of Finance, 1989)
ABSTRACT A firm raising capital in an initial public offering faces the problems of choosing between a firm‐commitment and a best‐efforts offering and of how to convey information about its value to potential investors. The offering method chosen affects both the firm's cost of obtaining capital and investors' perceptions about firm value. A partially pooling, partially separating equilibrium is found where high‐valued firms have information about their values revealed in a firm‐commitment offering, while low‐valued firms use best‐efforts offerings and are unable to distinguish themselves from other firms.